CONSUMER PROTECTION IN DIGITAL MARKETS: A Comparative Legal Analysis of E-Commerce Regulation in the United Arab Emirates and Indonesia - Benseghir, Mourad; Zerara, Aouatef; Bentria, Maamar (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
This study examines how the United Arab Emirates (UAE) and Indonesia regulate consumer protection within the expanding e-commerce environment, addressing the central question of how each jurisdiction safeguards consumer rights in a digital marketplace characterized by increasing online transactions and rising risks of fraud. Positioned within a comparative legal framework, the research evaluates the extent to which both countries’ regulations respond to modern digitaleconomy challenges. Using a normative and comparative approach, the paper analyses key statutory instruments, including the UAE’s Federal Law No. 15 of 2020 and Decree-Law No. 14 of 2023, alongside Indonesia’s Consumer Protection Law No. 8 of 1999, the ITE Law (2008), and Trade Law No. 7 of 2014. The analysis focuses on product information transparency, complaint mechanisms, personal data protection, and the regulation of cross-border electronic transactions. The findings show that the UAE provides stronger institutional safeguards, clearer digital-era obligations for suppliers, and a more effective enforcement structure. Indonesia, meanwhile, faces fragmented regulations and weaker supervisory mechanisms. The study concludes that Indonesia may strengthen its framework by adopting elements of the UAE model while adapting them to national principles such as Pancasila, thereby enhancing consumer trust and supporting sustainable digital economic growth. Studi ini mengkaji bagaimana Uni Emirat Arab (UEA) dan Indonesia mengatur perlindungan konsumen dalam lingkungan e-commerce yang terus berkembang, dengan fokus pada pertanyaan utama mengenai bagaimana masingmasing yurisdiksi melindungi hak konsumen di pasar digital yang ditandai oleh peningkatan transaksi online dan risiko penipuan yang semakin tinggi. Dalam kerangka hukum komparatif, penelitian ini mengevaluasi sejauh mana regulasi kedua negara merespons tantangan ekonomi digital modern. Menggunakan pendekatan normatif dan komparatif, makalah ini menganalisis instrumen hukum utama, termasuk Undang-Undang Federal UEA No. 15 Tahun 2020 dan Peraturan Pemerintah No. 14 Tahun 2023, serta Undang-Undang Perlindungan Konsumen Indonesia No. 8 Tahun 1999, Undang-Undang ITE (2008), dan Undang-Undang Perdagangan No. 7 Tahun 2014. Analisis ini berfokus pada transparansi informasi produk, mekanisme pengaduan, perlindungan data pribadi, dan regulasi transaksi elektronik lintas batas. Temuan menunjukkan bahwa UEA menyediakan jaminan institusional yang lebih kuat, kewajiban yang lebih jelas bagi penyedia layanan di era digital, dan struktur penegakan hukum yang lebih efektif. Indonesia, di sisi lain, menghadapi regulasi yang terfragmentasi dan mekanisme pengawasan yang lebih lemah. Studi ini menyimpulkan bahwa Indonesia dapat memperkuat kerangka kerjanya dengan mengadopsi unsur-unsur model UAE sambil menyesuaikannya dengan prinsip-prinsip nasional seperti Pancasila, sehingga meningkatkan kepercayaan konsumen dan mendukung pertumbuhan ekonomi digital yang berkelanjutan.